PENINGKATAN LITERASI AKSARA DI KELURAHAN PETUK BERUNAI, KOTA PALANGKA RAYA - Mualimin Mualimin; Defri Triadi; Ali Zainal Abidin; Agusti Sukma Wati; Dian Agustini; Elis Tania; Fathur Zami Isra; Martono Martono; Riska Suharno; Rosa Bella; Sartina Wati; Siti Qarimah (Journal of Social Outreach, 2022)
Covid-19 causes face-to-face learning cannot be carried out and is replaced by using online learning. Online learning causes new problems, especially in schools located in areas where internet access and transportation facilities are difficult, such as in Petuk Berunai, Palangka Raya City. Online learning in Petuk Berunai causes the teaching and learning process, especially in the aspects of reading and writing to experience problems. The effect is that many students have problems with reading and writing skills. Departing from these problems, this service activity aims to improve the reading and writing skills of elementary school students in Petuk Berunai, Palangka Raya City. This service is carried out using an Asset Based Community Development (ABCD) approach. The implementation of the literacy improvement program in the Petuk Berunai was carried out in four steps. First, conduct a reading ability test for students. Second, divide the class. Third, the implementation of the program starts from August 5 to 26, 2021. The learning program is carried out every Monday to Thursday. Meanwhile, from Friday to Sunday, motivational learning is carried out with a religious approach. Fourth, evaluate students' reading and writing abilities. Based on the comparison of pre-test and post-test assessments, it can be concluded that this service activity has been carried out well and that it has succeeded in improving the reading and writing skills of elementary school students in Petuk Berunai, Palangka Raya.Kata Kunci: Literasi Aksara, Petuk Berunai, Asset Based Community Development (ABCD)